Assessment of ESGO Quality Indicators in Cervical Cancer Surgery: A Real-World Study in a High-Volume Chinese Hospital - Ding, Yan; Zhang, Xuyin; Qiu, Junjun; Zhang, Jianfeng; Hua, Keqin (Frontiers in Oncology, 2022)
The ESGO developed a list of fifteen quality indicators for cervical cancer surgery in order to audit and improve clinical practice in 2020. However, data from the developing countries with high incidence rates of cervical cancer is still lacking. Therefore, we conducted a retrospective study of 7081 cases diagnosed as cervical cancer between 2014 and 2019 in a Chinese single center according to the quality indicators proposed by ESGO. A total of 5952 patients underwent radical procedures, with an average of 992.0 per year. All surgeries were performed or supervised by a certified gynecologic oncologist as surgical qualification grading system has been established. Compared with the low-volume group, patients in the high-volume group (≥15 cases/year) had a shorter hospital stay (P<0.001), more free surgical margins (P=0.031), and less complications (P<0.001), but the 5-year recurrence-free survival and overall survival rates were similar (P>0.05). Treatment was not planned at a multidisciplinary team meeting but with the consultation system. The required preoperative workup was incomplete in 19.7% of patients with pelvic MRI and 45.7% of patients with PET-CT. A total of 1459 (20.6%) patients experienced at least one complication after surgery. The CDC grade IIIb or higher complications occurred in 80 patients, accounting for 5.5% complications. The urological fistula rate within 30 postoperative days were 0.3%. After primary surgical treatment, 97.4% patients had clear vaginal and parametrial margins. After restaging FIGO 2009 to FIGO 2018 system, 14.7% patients with a stage T1b disease were T-upstaged. After a median follow-up of 42 months, recurrence occurred in 448 patients, and 82.1% patients recurred within 2 years. The 2-year RFS rate of patients with pT1b1N0 was 97.3% in 2009 FIGO staging system. Lymph node staging was performed in 99.0% patients with a stage T1 disease. After a primary surgical treatment for a stage pT1b1N0 disease, 28.3% patients received adjuvant chemoradiotherapy. Above all, most of quality indicators reached the targets, except four quality indicators. The quality indicators of ESGO should be popularized and applied in China to guarantee quality of surgery.